2020
DOI: 10.5194/isprs-archives-xliii-b4-2020-321-2020
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Emergency Evacuation in Building Fire

Abstract: Abstract. One of the main problems of rescue workers in confrontation of fired complex buildings is the lack of sufficient information about the building indoor environment and their emergency exit ways. Building information modeling (BIM) is a database for building a 3D model of building information to create a 3D building geometry network model. This paper has implemented some GIS and BIM integration analyses to determine the shortest and safest paths to people under fire risk and simulate their movement in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In fact, in the fifth Fresnel zone of all the propagation paths related to that receiver or transmitter, perturbation should be observed; therefore, in a receiver or transmitter, even if one of the related propagation paths is not perturbed, a radius of 300 km is not considered and there would be no possibility of earthquake occurrence in that area. A VLF/LF network is a combination of the shapes presented in GIS provide the spatio-temporal capabilities that can be used in many disciplines (Bayat et al, 2020;Eslamimezhad and Delavar, 2019). In this research a method for approximating the probable location of an earthquake occurrence based on the general configuration of a VLF/LF network is proposed which is called Intersection-Union method.…”
Section: Earthquake Spatial Prediction (Intersection-union Method)mentioning
confidence: 99%
“…In fact, in the fifth Fresnel zone of all the propagation paths related to that receiver or transmitter, perturbation should be observed; therefore, in a receiver or transmitter, even if one of the related propagation paths is not perturbed, a radius of 300 km is not considered and there would be no possibility of earthquake occurrence in that area. A VLF/LF network is a combination of the shapes presented in GIS provide the spatio-temporal capabilities that can be used in many disciplines (Bayat et al, 2020;Eslamimezhad and Delavar, 2019). In this research a method for approximating the probable location of an earthquake occurrence based on the general configuration of a VLF/LF network is proposed which is called Intersection-Union method.…”
Section: Earthquake Spatial Prediction (Intersection-union Method)mentioning
confidence: 99%
“…Dijkstra’s shortest path algorithm is used to identify the best route based on the risk score associated with each link. In [ 41 ]’s research, a comparison between the safest and shortest paths revealed that the safest route is often longer than the shortest route in most tested scenarios. In [ 15 ], Dijkstra’s shortest path algorithm is performed on a server to determine the evacuation route, and a control signal is sent to an 8 8 RGB Arduino matrix panel to show the evacuation direction.…”
Section: Related Workmentioning
confidence: 99%
“…One of the major determinants of fire evacuation in built environments is facility physical features. Building Information Modeling (BIM) provides graphical interface for user interaction and geometric information of the building scene, which acts as a data input for fire evacuation simulation computing (Bayat et al 2020;Bina and Moghadas 2020;Chen and Chu 2016;Chen and Huang 2014;Chen et al 2018;Cheng et al 2017;Choi et al 2014;Fu and Liu 2020;Isikdag et al 2013;Li et al 2014;Ma and Wu 2020;Mirahadi et al 2019;Rüppel et al 2010;Sun and Turkan 2020;Wang et al 2012;Yenumula et al 2015). Bi et al (2013) stated that BIM has the advantage of 3D visual modeling and detailed geometric information model of the building structure, components, equipment's etc.…”
Section: Facility Geometrical Analysismentioning
confidence: 99%